Nasal microbial diversity is associated with survival in piglets infected by a highly virulent PRRSV-1 strain - Pau Obregon-Gutierrez; Martí Cortey; Gerard E. Martín-Valls; Hepzibar Clilverd; Florencia Correa-Fiz; Virginia Aragón; Enric Mateu (Animal Microbiome)
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) is a major threat to swine industry worldwide, especially virulent variants arising during the last years, such as Spanish PRRSV-1 Rosalia strain. The role of the nasal microbiota in respiratory viral infections is still to be unveiled but may be promisingly related with the health status of the animals and thus, their susceptibility. The goal of this project was to study the nasal microbiota composition of piglets during a highly virulent PRRSV-1 outbreak comparing animals that died due to the infection with animals that survived it. The microbiota composition was inferred by V3–V4 regions of the 16S rRNA gene sequencing and bioinformatics analysis. To deepen the analysis, we added samples taken from piglets before the outbreak as well as from the sows giving birth to piglets under study. Results Piglets that survived the PRRSV-1 outbreak reported a more diverse and different nasal microbiota at three weeks of age compared to piglets dying, which was highly related with the litter of origin and the sow of the piglets. In addition, a high abundance of classical swine nasal colonizers belonging to genera such as Bergeyella, Glaesserella, Neisseria and Moraxella (among others), was related with good outcome. On the other hand, a dysbiotic community dominated by Escherichia and a different clade of Moraxella was found in piglets with bad outcome. Moreover, samples taken before the outbreak showed similar dynamics prior to virulent PRRSV-1 arrival, suggesting that microbiota-related susceptibility was already occurring in the animals and that the increase in mortality seen was related to the new highly virulent strain. Conclusion Our study suggests that the susceptibility to an infection such as PRRSV could be related to the nasal microbiota composition at the moment of infection and may serve as starting point to explore animal resilience. Since the dysbiosis detected as an initial response to infection may be not specific for this virus, further investigations should explore this phenomenon in the context of other viral infections.